2017
DOI: 10.13080/z-a.2017.104.021
|View full text |Cite
|
Sign up to set email alerts
|

Vandenyje tirpių angliavandenių kaupimasis kviečio žiedynkotyje ir jų ryšys su morfoanatominiais bei produktyvumo požymiais

Abstract: Water-soluble carbohydrates (WSC) accumulating in internodes of the wheat stem can be a consequential contributor to grain filling, especially under stress conditions. In this study the WSC content and the WSC specific content (WSCSC) per unit of length were determined in the uppermost internode (peduncle) of the main stem at 10 days after anthesis across 44 wheat genotypes in two-year field trials. The defoliation was done at 10 days after anthesis by cutting off all leaf blades and defoliated plants were gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…But our study has shown that WSCs are directly associated with grain yield under limited water supply condition. Similar correlation was also noticed by Seslija et al (2017) and Hou et al (2018) where wheat genotypes were evaluated for grain yield attributing traits.…”
Section: Discussionsupporting
confidence: 78%
“…But our study has shown that WSCs are directly associated with grain yield under limited water supply condition. Similar correlation was also noticed by Seslija et al (2017) and Hou et al (2018) where wheat genotypes were evaluated for grain yield attributing traits.…”
Section: Discussionsupporting
confidence: 78%
“…The experimental material comprised three groups of winter or facultative common wheat (Triticum aestivum L.) cultivars and breeding lines: standard genotypes (2 entries used in the wheat-breeding program at MRIZP), F6:7 families (8 entries) and parent genotypes used to make the F6:7 families (10 entries). The wheat genotypes evaluated in the present study were selected based on previously conducted two-year trials in which initially sixty-one, and then forty-four wheat genotypes were evaluated [7,[21][22][23]. Genotype names, origin, and parentage are given in Table 1.…”
Section: Genotypesmentioning
confidence: 99%